2017
DOI: 10.3390/inventions2010004
|View full text |Cite
|
Sign up to set email alerts
|

Review of Ship Microgrids: System Architectures, Storage Technologies and Power Quality Aspects

Abstract: Ship microgrids have recently received increased attention, mainly due to the extensive use of power electronically interfaced loads and sources. Characteristics of these microgrids are similar to islanded terrestrial microgrids, except the presence of highly dynamic large loads, such as propulsion loads. The presence of such loads and sources with power-electronic converter interfaces lead to severe power quality issues in ship microgrids. Generally, these issues can be classified as voltage variations, frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(78 citation statements)
references
References 65 publications
0
77
0
1
Order By: Relevance
“…Microgrids have been defined in various ways, all of which present them as a smaller version of the electric power grid [46][47][48][49][50][51][52][53]. They are a localized arrangement of electrical sources and loads that operate in connection to the existing grid system, i.e., the on-grid mode, and can also operate as a stand-alone energy system when disconnected from the grid, i.e., off-grid mode.…”
Section: Microgrid Technologiesmentioning
confidence: 99%
“…Microgrids have been defined in various ways, all of which present them as a smaller version of the electric power grid [46][47][48][49][50][51][52][53]. They are a localized arrangement of electrical sources and loads that operate in connection to the existing grid system, i.e., the on-grid mode, and can also operate as a stand-alone energy system when disconnected from the grid, i.e., off-grid mode.…”
Section: Microgrid Technologiesmentioning
confidence: 99%
“…Segregated power distribution is a system that separates between the main propulsion system and the auxiliary system [6]. This system has advantages in terms of installation, maintenance, and operation.…”
Section: Introductionmentioning
confidence: 99%
“…However, this is likely to be influenced by the size and amount of ca rgo operations required for the ship. The corresponding figures for Reefer ships, Ro-Ro ships, tankers and Bulk cargo ships are on average, 2 MW, 0.7 MW, 5 to 6 MW and 0.3 to 1 MW [21].…”
Section: Ship Service Electrical Loading Valuementioning
confidence: 99%
“…The bar chart plots the Percentage of running hours against the Main Engine load. The exemplary load profiles of a harbor tug with two forward thrusters supplied by a 2040 KW diesel engine that tows container ships is shown in Figure 4 while that of a passenger motor ferry with a 50 KW service load and driven by 2 × 470 KW gas engines that does a 40-min to and fro journey [21] regularly is as below in Figure 5. It is observed that the load variation has a more evenly balanced distribution approaching a typical normal distribution in the case of the container ships while smaller vessels such as tugs and ferries have a more skewed profile.…”
Section: Loading Conditions Of Shipsmentioning
confidence: 99%
See 1 more Smart Citation